Locating genes controlling allelopathic effects against barnyardgrass in upland rice - Jensen, Louise Bach; Courtois, Brigitte; Shen, Lishuang; Li, Zhikang; Olofsdotter, Maria; Mauleon, Ramil P. (Wiley, 2001)
To understand the genetic control of allelopathy in rice (Oryza sativa L.), quantitative trait loci (QTL) mapping was performed using a population of 142 recombinant inbred lines derived from a cross between cultivar IAC 165 (japonica upland variety) and cultivar CO 39 (indica irrigated variety). The map contained 140 DNA markers. The relay seeding technique, which is a laboratory bioassay measuring the inhibition in weed root growth due to the presence of rice seedlings, was used to evaluate the allelopathic effect of the rice lines. Cultivar IAC 165 showed strong and consistent allelopathic activity against barnyardgrass [Echinochloa crus‐galli (L.) Beauv.], whereas CO 39 was weakly allelopathic. Transgressive segregation for allelopathic activity in both directions was observed in the population. No significant correlation was found between root morphology of the lines and their allelopathic potential, suggesting that allelopathy in rice was under genetic control independent from root morphology. Four main‐effect QTLs located on three chromosomes were identified, which collectively explained 35% of the total phenotypic variation of the allelopathic activity in the population. One pair of digenic epistatic loci, not involving any of the main‐effect loci, was also detected. Once confirmed, these QTLs may be useful for genetic improvement of allelopathy in rice using marker‐assisted selection.